Multicultural Education is a Strategy for Building Social Harmony Amidst the Diversity of Cultural and Religious Identities in Indonesia - Zulfa, Kufita Indi; Aulina, Tariska Dina; Liana, Yogi Apri (Proceedings Series on Social Sciences & Humanities, 2025)
Indonesia as a multicultural country consisting of various ethnicities, religions, races and cultures faces great challenges in building social harmony amidst inherent differences. Multicultural education exists as a strategic approach in responding to this challenge by instilling the values of tolerance, respect for differences and social justice from an early age. This article examines the role of multicultural education in the Indonesian national context, by highlighting inclusive educational policies, curricula and pedagogical practices in the school environment. The method used is a literature review with a descriptive qualitative approach. The results of the study show that the consistent implementation of multicultural education can strengthen national identity, reduce the potential for horizontal conflict, and create space for healthy dialogue between communities. However, challenges still arise in the form of cultural resistance, minimal teacher training, and limited adaptive curriculum. Therefore, synergy is needed between the government, educators and society in creating harmony in diversity through a humanist and transformative education system.